1997
DOI: 10.1139/z97-826
|View full text |Cite
|
Sign up to set email alerts
|

Vocal solicitation of heat as an integral component of the developing thermoregulatory system in young domestic chickens

Abstract: Young domestic chickens (Gullus gullus) were able to regulate their body temperature in a laboratory setting, where vocalizations triggered a period of rewarming (35°C) in an otherwise cold environment. Vocal solicitation of a rewarming period functioned in an analogous manner to the parental brooding response to a vocalizing chick. The number of vocally generated rewarming bouts increased if the cold-challenge temperature was decreased from 20 to 5°C. The body temperature and ambient temperature maintained du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Several considerations lead to the expectation of some degree of reciprocity between autonomic thermogenesis and behavioral means of Tb control (Weiss& Laties, 1961; Myhre, 1978; Bugden and Evans, 1997; Schlader et al, 2009). For example, lower vertebrates with minimal endothermy rely heavily on behavioral means for Tb regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Several considerations lead to the expectation of some degree of reciprocity between autonomic thermogenesis and behavioral means of Tb control (Weiss& Laties, 1961; Myhre, 1978; Bugden and Evans, 1997; Schlader et al, 2009). For example, lower vertebrates with minimal endothermy rely heavily on behavioral means for Tb regulation.…”
Section: Discussionmentioning
confidence: 99%
“…In a series of experiments in the 1990s, Evans showed that avian embryos do so using acoustic signals. In a number of precocial and altricial species, embryos increase calling rate when their temperature deviates from the optimal incubation temperature (Evans, 1990;Evans et al, 1995;Bugden and Evans, 1997) (Figure 1). Evans demonstrated that if parents respond to calls by resuming incubation, embryonic vocalisations can effectively maintain optimal incubation temperature (Evans, 1990;Evans et al, 1995).…”
Section: Vocal Thermoregulation: Honest Signal Of Embryonic Thermal Nmentioning
confidence: 99%
“…In relation to thermoregulation, chicken vocalisations have been shown to have specific patterns when chicks are exposed to cold stress [22]. Furthermore, vocal solicitation of heat, forms an integral part of the development of the thermoregulatory system of young chickens [23]. Finally, the thermal comfort of chicks has been shown to have links with the amplitude and frequency of calls [24].…”
Section: Monitoring Of Vocalisations Of Chickensmentioning
confidence: 99%